2011
DOI: 10.1128/aem.00324-11
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Effect of Host Genetics on Levels of Lactobacillus johnsonii Bacteria in the Mouse Gut

Abstract: The gut microbiota is strongly associated with the well-being of the host. Its composition is affected by environmental factors, such as food and maternal inoculation, while the relative impact of the host's genetics have been recently uncovered. Here, we studied the effect of the host genetic background on the composition of intestinal bacteria in a murine model, focusing on lactic acid bacteria (LAB) as an important group that includes many probiotic strains. Based on 16S rRNA gene genotyping, variation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 57 publications
(68 reference statements)
3
40
0
Order By: Relevance
“…The composition of the GM has previously been shown to be influenced by multiple factors including environment and host genetics [8], [27][31]. The latter seems to be a major force driving the GM differences between the various mice and human clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the GM has previously been shown to be influenced by multiple factors including environment and host genetics [8], [27][31]. The latter seems to be a major force driving the GM differences between the various mice and human clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Two such studies (Benson et al, 2010;Buhnik-Rosenblau et al, 2011) found ties between host genetics and Lactobacillus in mice. Another study (Alexander et al, 2006) in which mice from 23 inbred strains were inoculated with and tested for the altered Schaedler's flora using specific quantitative PCR assays noted significant differences for these species.…”
Section: Discussionmentioning
confidence: 99%
“…If the genetic background does not match well, even the already released probiotics could not survive for an extended time. For example, based on 16S rRNA gene genotyping, Buhnik-Rosenblau et al (2011) found that L. johnsonii (a potentially probiotic bacterium) appeared at significantly higher levels in C57BL/6J versus BALB/c mouse feces, their offspring presented similar L. johnsonii levels. However, after oral administration, the L. johnsonii level decreased rapidly in the BALB/c gut, suggesting that some selective force does not allow its persistence at higher levels.…”
Section: Linking Gut Virome and Bacterial Communities With Complex DImentioning
confidence: 93%